Analisis Sidik Jari Kromatografi Lapis Tipis Secara Kemometrik Daun Tumbuhan Anting-Anting (Acalypa Indica L.) Berdasarkan Lokasi Tumbuh - Hidayaty, Alfianita Nuril; Hayati, Elok Kamilah (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2024)
Anting-anting plant (Acalypha indica L.) is a tropical plant with abundant secondary metabolite content, so its content can be used as traditional medicine. One of the secondary metabolites is influenced by the location of growth in different groups of compounds and levels. Information related to secondary metabolites can be used for quality control. This study aims to determine the effect of differences in growing locations on levels and secondary metabolites in the Tuban, Bojonegoro, and Ngawi regions. The method used is Thin Layer Chromatography (TLC) followed by the Orange 3.32 Principal Component Analysis (PCA) chemometric method to obtain the grouping and concentration of each sample. The results of the TLC separation obtained 10 sample spots from the Tuban area, 10 sample spots from the Bojonegoro area, and 13 sample spots from the Ngawi area. PCA multivariate analysis explained that the total data variation was 91% (PC 1= 52.5%; PC 2= 38.5%). These results indicate that there are differences in the levels and groups of active compounds with different Area Under Curve (AUC) values for each sample of the earring leaf extract.